PERAN ATF (ASEAN TOURISM FORUM) TERHADAP UPAYA PROMOSI WONDERFUL INDONESIA - Wahyuni, Mayang Sri; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study attempts to outline anything ATF (ASEAN Tourism Forum) programs in an effort to promote Wonderful Indonesia. And also will explain how ATF programs in an effort to promote Wonderful Indonesia. The methodology used is qualitative study. This study focused to talk the efforts of ATF to promote Wonderful Indonesia. Second, researchers feel the need to give time limit to phenomena or problem to check such as in 2011-2017.This research use a pluralism perspective and international organizations theory. The level analysis is international organizations, this reseach also includes the concept of tourism as the point of views this research.The study concluded that ATF has done his role as international forums in an effort to promote Wonderful Indonesia. ATF in collaboration with Indonesian Government to promote Indonesian tourism through Wonderful Indonesia brand.Keywords: ATF (ASEAN Tourism Forum), Tourism, Wonderful Indonesia